Riqueza e diversidade de pequenos mamíferos não voadores na Mata de Tabuleiro capixaba - Conde, Luciana Onécia Machado (2016)
Non volant small mammals have showed different answers faced with the environmental modifications, either agriculture or agro-ecosystems. This situation can lead to disequilibrium between opportunistic species and the species that are sensitive to the environmental changes and may result in a replacement or overlapping species. Mostly,small mammals species have a dependency relationship with the forest, because they develop an important paper in these environments such as seeds and insects predators, seed dispersers and as base of the food chain to other vertebrates, reasons why, several species of this animals are considered good indicators of landscape and habitat changes when a forest continue to suffer area loss. The remaining fragments become isolated, and the number of species will change mainly because of the effects of areas reduction and distance of continuous forest between its forest fragments. Over time, the diversity tends to decrease, and eventually, can reach a new state of equilibrium, however will be less diverse. In State of Espírito Santo, the mastofauna is still poorly studied, especially as regards to their distribution. Facing the reduction of trays Forest in isolated fragments, the risk of defaunation and the absence of studies of small mammals in northern ES, this study had the objectives: (i) To check the composition of species of non volant small mammals in three Conservation Unities in the Northern of Espírito Santo, (ii) To examine the composition of these three Conservation Unities and, (iii) to evaluate whether the results vary depending on the category of conservation.